2018
DOI: 10.1007/s10919-018-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

You are What You Wear: Unless You Moved—Effects of Attire and Posture on Person Perception

Abstract: While first impressions are often based on appearance cues, little is known about how these interact with information from other channels. The present research aimed to investigate the impact of occupational stereotypes, evoked by attire, as well as posture on person perception. For this, computer animation was used to create avatars with different types of attire (nurse, military, casual) and posture (open, closed). In Study 1 (N = 164), participants attributed significantly more empathy to avatars wearing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…From prior studies, only appearance or sexual visual symbols were indicated as the reason for there being an impression of sexuality (Huo and Yuan, 2017 ; Wirtz et al, 2018 ). Küster et al showed that participants judged female virtual agents by what they wore (Küster et al, 2019 ). Their experiment was conducted without any verbal information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From prior studies, only appearance or sexual visual symbols were indicated as the reason for there being an impression of sexuality (Huo and Yuan, 2017 ; Wirtz et al, 2018 ). Küster et al showed that participants judged female virtual agents by what they wore (Küster et al, 2019 ). Their experiment was conducted without any verbal information.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that what an agent and human wear affects the interaction. Küster et al showed that humans judged virtual agents by what they wear without other non-verbal information (Küster et al, 2019 ). Their study used female and male virtual agents.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, mimicry to happy faces is often still present (e. g., Bourgeois & Hess, 2008;Van der Schalk et al, 2011;Seibt et al, 2013). Happy smiles are a very potent signal of the desire to affiliate (Knutson, 1996) and there is evidence that state information on a behavioral intentions tends to override more stable sources of information (Küster, Krumhuber, & Hess, 2019). Thus, unless the target is judged very negatively (Likowski et al, 2008) the affiliative state signal of smiling may suffice to motivate affiliation.…”
Section: Mimicry Is Goal-dependentmentioning
confidence: 99%
“…As noted earlier, emotional expressions are perceived as social signals that tell others something about the person and the situation ( Hess and Hareli, 2019 ). In fact, the situational information provided by an emotional expression is often dominant over character information as it is more proximal to the evaluation ( Küster et al, 2019 ). However, in this study, this was only inconsistently the case.…”
Section: Discussionmentioning
confidence: 99%